2019
DOI: 10.1111/aej.12372
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients with endodontically treated teeth: A systematic review

Abstract: This systematic review aimed to appraise the quality of life of patients with restored endodontically treated teeth. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were employed. The specific PEO question was as follows: population: patients who were healthy individuals ≥18 years old and required endodontic treatment; exposure: endodontic treatment with a coronal restoration with at least 6 months in occlusal function; and outcome: quality of life of patients. Databases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Regardless of the complex interplay between peripheral sensitization and CS, patients undergoing either nonsurgical or surgical endodontic treatment often report the alleviation of symptoms and increased quality of life 9 . Unfortunately, despite the high success rates of the alleviation of symptoms after endodontic therapy, there are approximately 5% of patients who present with persistent pain despite adequate treatment 10 .…”
Section: Significancementioning
confidence: 99%
“…Regardless of the complex interplay between peripheral sensitization and CS, patients undergoing either nonsurgical or surgical endodontic treatment often report the alleviation of symptoms and increased quality of life 9 . Unfortunately, despite the high success rates of the alleviation of symptoms after endodontic therapy, there are approximately 5% of patients who present with persistent pain despite adequate treatment 10 .…”
Section: Significancementioning
confidence: 99%
“…Recent systematic reviews have demonstrated that root canal treatment can positively impact the OHR-QoL, but these reviews have also concluded that the lack of well-designed trials impairs the possibility of providing strong evidence (Antunes et al 2018, Leong & Yap 2019, Neelakantan et al 2020. In fact, most clinical trials evaluate changes on OHRQoL until only a few days after the end of endodontic treatment (Neelakantan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Equally, greater certainty is required on periapical radiolucencies that are resolving slowly, and whether they are likely to become a risk in susceptible patients. Other parameters related to quality of life and patient perceptions should also be considered in the decision‐making process before planning further treatment (Liu et al , Leong & Yap ).…”
Section: Classification Of Outcomementioning
confidence: 99%